Fragile Futures: How Socioeconomic Factors Shape Severe Wasting in Toddlers - Devitasari, Amelia Putrie (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study examines the influence of socioeconomic factors on the prevalence of wasting among toddlers in Boyolali Regency during 2014–2023. Despite improvements in economic indicators such as Gross Regional Domestic Product (GRDP) and per capita income, progress in reducing wasting has lagged behind neighboring areas. Using multiple linear regression analysis, the study investigates the relationship between GRDP, poverty, food prices, per capita income, and the number of children on severe wasting rates. The study uncovers that poverty and food prices have a significant positive impact on wasting, while per capita income has a significant but negative impact, suggesting that increased income worsens wasting due to inequality and shifting consumption priorities. Whereas, GRDP and the number of children show no significant relationship with wasting. The study concludes that poverty and food prices require targeted interventions to address inequality and promote nutrition education. Policy implications include improving social assistance programs and enhancing access to quality food. This research contributes to understanding socioeconomic determinants of malnutrition and supports local government strategies to improve child nutrition.